Proyecto de factibilidad para la creación de una Cooperativa de producción de abono orgánico en base a los residuos de la caña de azúcar ubicada en la parroquia morales del cantón Portovelo provincia de El Oro - Clavijo Casco, Andrés Emilio (2015)
This project examines the feasibility of creating a production cooperative of Organic Fertilizer based on sugarcane waste, located at the Morales parish in Portovelo city, El Oro province, analyzing technical aspects of the market, and profitability. The first part covers the investigation problem, with its objectives, which must be established to be clear about the project. The second part includes a market analysis considering the supply, the demand, and the prices. This will allow us to identify unsatisfied needs in the market, and the amount of organic fertilizer that people would buy at a certain price. The third part is the technical study; it includes the optimal size and location of the project, production processes, physical distribution of areas and equipment, organizational and legal aspects to create the production cooperative. The fourth part is an economic and financial analysis of operating conditions, determining total costs and initial investment, working capital, financing, initial balance sheet, income statement projected to five years, breakeven point and the rate that investors wish get in the project, here we have all figures to carry out the financial evaluation. After obtaining market data, and all costs of installation and operation of the cooperative, we determine the investment profitability under the internal rate to return (IRR) and net present value (NPV) criteria, this part deserves great importance, because it allows us to decide if the project is achievable or not. Finally we have to determine some conclusions and recommendations based on the data obtained in each chapter.